Development of sustainable Tamanu industry in Indonesia based on the green waqf model through sharia crowdfunding platforms - M. Khoirul Fikri; Rizky Andrean (Center for Islamic Economics and Development Studies [P3EI], 2023)
Purpose – This study aims to describe how the green waqf-based model through sharia crowdfunding platform for sustainable Tamanu industrial development in Indonesia. The Tamanu industry is a sustainable industry engaged in the agricultural sector (agro-based industry) based on the utilization of Tamanu plants (Calophyllum inophyllum), which can consist of the plantation industry, biofuel industry and pharmaceutical and cosmetic industry.Methodology – This research uses a descriptive qualitative approach in the form of a literature study of various literature relevant to the research topic. This research is a type of development research to formulate a model to answer the existing problems on how to find funding solutions for developing the Tamanu industry in Indonesia.Findings – A green waqf-based financing model through a Sharia crowdfunding platform can be a solution to financing the sustainable Tamanu industry.Implications – Through this model, the potential of existing waqf can be further maximized to impact the community's economic progress and environmental sustainability through developing a sustainable Tamanu industry.Originality – This model is an elaboration between studies on renewable energy, Islamic philanthropy, Sharia financial technology, and green industry to support achieving sustainable development goals in Indonesia.